2006
DOI: 10.1002/mabi.200600052
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Model Bladder Extracellular Matrix Combining Disulfide Cross‐Linked Hyaluronan with Decellularized Bladder Tissue

Abstract: [Image: see text] In this work we investigate the feasibility of modifying porcine-derived BAM to include HA with a view to developing a model, artificial extracellular matrix for the study of bladder cell-matrix interactions. HA-DPTH was incorporated into BAM disks and then cross-linked oxidatively to a disulfide containing hydrogel. Disks were seeded with bladder smooth muscle cells (BSMC) and UEC under three culture configurations and incubated for 3, 7, and 14 d. At each time point, matrix contraction was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 35 publications
(41 reference statements)
0
15
0
Order By: Relevance
“…To the best of our knowledge, there is no precedent for the investigation of in vivo host response to an ECM impregnated with a HA hydrogel, limiting comparison of our results to previous work. However, in one recent study, Brown et al showed that bladder ECM treated with disulfide cross-linked, thiol-modified HA facilitated and expedited the infiltration of bladder smooth muscle cells into bladder ECM in cell culture [59]. Since disulfide cross-linking is reversible and the incorporated HA could be leached or degraded over time (unlike dityramine cross-linking), this result is consistent with our observation of heightened cellularity in TS-HA treated fascia without cross-linking.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there is no precedent for the investigation of in vivo host response to an ECM impregnated with a HA hydrogel, limiting comparison of our results to previous work. However, in one recent study, Brown et al showed that bladder ECM treated with disulfide cross-linked, thiol-modified HA facilitated and expedited the infiltration of bladder smooth muscle cells into bladder ECM in cell culture [59]. Since disulfide cross-linking is reversible and the incorporated HA could be leached or degraded over time (unlike dityramine cross-linking), this result is consistent with our observation of heightened cellularity in TS-HA treated fascia without cross-linking.…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of GAGs is substantial as they are important in morphogenesis, cell shape changes and motility (26). Contrary to collagen, GAGs levels in decellularized livers were elevated about 5-and 8-fold, respectively, compared to native livers.…”
Section: Discussionmentioning
confidence: 95%
“…In addition variables arise depending upon the tissue used, the species from which the tissue/organ is isolated from and the terminal sterilisation procedures used [43]. Such decellularized tissues and organs have been used to culture cells in vitro to better understand disease pathogenesis as well as drug delivery [44,45].…”
Section: Decellularized Tissues/organsmentioning
confidence: 99%